Program Pemberdayaan Mahasiswa Melalui Bimbingan Teknis Penulisan Artikel Jurnal Ilmiah - Demitra Demitra; Sarjoko; Pancarita (Jurnal Pengabdian Kampus, 2022)
This program aims to provide knowledge and skills for students who are writing a thesis at the Mathematics Education Study Program, FKIP University of Palangka Raya. The achievement target is that students are able to write scientific articles on research results in their thesis. Partners and the target audiences are 16 students who are writing a thesis at the Mathematics Education Study Program, FKIP University of Palangka Raya. Technical guidance will be held for 3 days from 08–11 October 2021 online using the Google Meet platform. Activities carried out during the stages of socialization, technical guidance, clinical guidance, and evaluation of manuscripts. The evaluation of the manuscript uses the assessment sheet for the relevant scientific journal articles, and the scientific journal accreditation guide (Arjuna). The results of providing technical guidance are as follows. Of the 16 articles, there are 4 articles whose findings are adequate and contribute to the development of science and technology. There are 6 draft articles that have been made by students, which consist of 3 draft articles with all the sub-chapters written by students waiting for the final exam schedule. Almost all draft articles have not met an adequate number of references for a scientific journal article. While the other three are draft articles that have met the requirements to be submitted for publication in scientific journals.